Multi-keyword partial matching algorithm based on text fragments - LIAO Wei-qi; ZOU Wei (Tongxin xuebao)
Network content detection based on Key words in security gateway often need to reassemble the TCP packets and even the whole file, which will cause a long delay. In order to resolve the problem, a new concept of pattern par-tial-matching based on text fragments was presented. A novel multi-keyword partial matching algorithm was also de- signed and realized which could detect the fraction of keywords in data block without re-flow or re-file. Comparing to the normal multi-keyword matching algorithm, it was proved by experiments that the false negative of the algorithm is zero, and the false positive rate is little enough when the data block is large enough.